Necessary measures to prevent the risk of flooding in urban centers in the Wadi Inawen basin in Morocco: Applied study - Neddama, Ali; El-Bazoui, Jaouad; Bouberria, Abdelouahed (Journal of natural sciences, life and applied sciences, 2024)
The Inaoun Basin depression constitutes one of the Moroccan areas threatened by the risk of flooding in a number of locations, due to its climatic characteristics characterized by the abundance and often concentration of precipitation, and also the concentration of most urban centers on the banks of the valleys, or they are penetrated by a group of a group of reefs that feed from the slopes and highlands. neighboring, This makes it constantly exposed to the risk of flooding, especially with the increase in uncontrolled urban expansion that has occurred in recent years. Which makes the phenomenon worse in the absence of technical solutions capable of preventing hydrological dangers. The occurrence of these disasters requires allocating huge and unexpected financial budgets, and their occurrence contributes to creating social and psychological crises. They also require the competent authorities to allocate aid to the affected areas.  For all these considerations, we decided to address the issue of flood risk and management methods in urban centers in the Inawon Basin depression, and we addressed the issue according to the factors contributing to the formation of floods in this area, and the measures taken to protect these centers from their risks.
Keywords: basin; floods; hydrology; centers; urban; risks